Applications of GPS and Equipment Monitoring Technology to Blasting Operations in Surface Mining (International Society of Explosives Engineers, 1995)
The objective of current efforts by AQUILA Mining Systems Ltd. is the continued development of computer-based systems and techniques to automatically process and interpret monitored performance data from surface blasthole drills and mining shovels, and the management and coordination of these pieces of equipment by GPS (Global Positioning Systems).